1997
DOI: 10.1002/(sici)1520-6793(199710)14:7<637::aid-mar1>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal exchange in rural communities: Consumers' inducements to inshop

Abstract: Although consumer -retailer exchange behavior has been studied for many years, its treatment has not accounted for factors relating to reciprocal exchange intentions. This article defines reciprocity as the degree to which individuals expect cooperative action, and places reciprocity within the overall framework of consumer -retailer market exchange. In addition, it presents results of an exploratory study of rural consumers' reciprocal intentions to shop with local retailers, indicating that levels of satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 0 publications
2
52
0
Order By: Relevance
“…Reciprocity contributes to social capital through network members who amass favors, which can be called upon as resources when needed (Portes & Sensenbrenner, 1993). Miller and Kean (1997) refer to community reciprocity as an expected exchange between local consumers and local retailers. They found that local consumers were more likely to shop with local retailers when those retailers expressed a high level of support for the community.…”
Section: Social Capitalsupporting
confidence: 67%
See 1 more Smart Citation
“…Reciprocity contributes to social capital through network members who amass favors, which can be called upon as resources when needed (Portes & Sensenbrenner, 1993). Miller and Kean (1997) refer to community reciprocity as an expected exchange between local consumers and local retailers. They found that local consumers were more likely to shop with local retailers when those retailers expressed a high level of support for the community.…”
Section: Social Capitalsupporting
confidence: 67%
“…Reciprocity is measured using a five item scale, three items from Miller and Kean (1997), achieving a reliability of 0.85, and Frazier (2000, unpublished data) who reported a reliability of 0.87. Each item was measured on a seven-point Likert scale anchored from "strongly disagree" to "strongly agree".…”
Section: Methodsmentioning
confidence: 99%
“…The norm prescribes that one should help those who have helped him/her in the past and retaliate against those who have been detrimental to his/her interests. Reciprocity has been used in social psychology to explain a wide range of phenomena, such as attitude change (Cialdini, Green, & Rusch, 1992), intimacy in close relationships (Surra & Longstreth, 1990), interpersonal perception (Kenny, Bond, Mohr, & Horn, 1996), altruism (Krebs, 1975), aggression (Robarchek & Robarchek, 1998), cooperation (Komorita & Parks, 1999), intergroup interactions (Goren & Bornstein, 1999), consumer shopping (Miller & Kean, 1997), restaurant tipping (Rind & Strohmetz, 1999), and gift giving (Cialdini, 1988).…”
Section: The Norm Of Reciprocitymentioning
confidence: 99%
“…Reciprocity involves mutual exchange of favors and is characterized by mutual reinforcement and help by the two parties (Gouldner, 1960;Miller & Kean, 1997).…”
Section: Benevolencementioning
confidence: 99%
“…We define reciprocity as the mutual exchange of helping behaviors between importers and exporters. Reciprocity in exchange relationship facilitates bonds between exchange partners and reflects caring intention for the well being of exchange partners (Houston & Gassenheimer, 1987;Miller & Kean, 1997).…”
Section: Introductionmentioning
confidence: 99%